1983
DOI: 10.1046/j.1537-2995.1983.23283172849.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Wj: an autoantibody that defines a high‐incidence antigen modified by the In(Lu) gene

Abstract: An IgG autoantibody, named anti-Wj, reacts with all random and most selected red cell samples. It does not agglutinate cells of Lu(a-b-) type caused by the In(Lu) dominant inhibitor gene, but cells of recessive Lu(a-b-) type are reactive. These data establish that synthesis of the Wj antigen is suppressed by the In(Lu) gene, but it is not a part of the Lutheran blood group system. The Wj antigen is not well developed on fetal red cells. This example of auto anti-Wj is a non-complement-binding IgGl protein that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…This Lutheran inhibitory In(Lu)l gene is an autosomal gene, not linked to the Lutheran loci, which in the heterozygote, suppresses almost totally the expression of Lutheran antigens (2)(3)(4)(5)(6)(7). Partial penetrance of the gene is also believed to account for some phenotypes with weak expression of Lutheran antigens, which is also inherited as a dominant trait (4,8). The In(Lu) gene is also known to reduce expression of other erythrocyte antigens, such as Auberger (Au'), Pi, and i (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Lutheran inhibitory In(Lu)l gene is an autosomal gene, not linked to the Lutheran loci, which in the heterozygote, suppresses almost totally the expression of Lutheran antigens (2)(3)(4)(5)(6)(7). Partial penetrance of the gene is also believed to account for some phenotypes with weak expression of Lutheran antigens, which is also inherited as a dominant trait (4,8). The In(Lu) gene is also known to reduce expression of other erythrocyte antigens, such as Auberger (Au'), Pi, and i (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the action of the In(Lu) gene remains unknown; it has been postulated that it may turn off production of a precursor or backbone molecule required for expression of the Lu, Au', P1, and i antigens or that the In(Lu) gene may code for an enzyme that modifies the substrate of the Lu, Aua, Pi, and i gene products, thus reducing or preventing expression of these antigens (11). Both Lua and Lub antigens have been shown to vary in strength from one family to another, such that a heterozygote for Lub in one family may express as much antigen as a homozygote in another family (4,8,12). This phenomenon is also thought by some to reflect variants of the In(Lu) gene.…”
Section: Introductionmentioning
confidence: 99%
“…The Anton antibody has the same reac tivity as the monoclonal antibodies reported recently by Knowles et al (7] and the auto antibody anti-Wj reported by Marsh et al [9]. It provides the first human allo-antibody capable of distinguishing the two Lu(a-b-) phenotypes.…”
mentioning
confidence: 54%
“…The recessive category arises from the inheritance of two amorphic Lu genes [5], whereas the dominant category results from the inheritance of the autosomal dominant suppressor gene In(Lu) [6], Red cells with the dominant Lu(a-b-) phenotype, unlike those of the recessive type, have very weak Luther an antigens which may be detected by adsorption/elution tests. They have depressed i and Pi antigens and fail to react with anti-Aua, Anton antibody [3], anti-Wj [4], and with the two monoclonal antibodies M447 and H86 [2], all of which react normally with the recessive type.…”
Section: Introduction Resultsmentioning
confidence: 99%